Analyzing competition between the high speed train and alternative modes: The case of the Madrid-Zaragoza-Barcelona corridor - Concepción Román; Raquel Espino; Juan Carlos Martin (Journal of Choice Modelling, 2010)
While there have been many studies of urban travel demand, little attention has been paid to the analysis of inter-urban rail travel demand. Studies of inter-urban rail demand usually focus on assessment through the conventional cost benefit analysis of this type of investments, in which the emphasis is on the cost side. However, the analysis of the potential benefits, bearing in mind the intermodal competition, is usually neglected. This paper analyzes the potential competition of the high speed train (HST) with the main competing modes on the Madrid-Barcelona route, where a new HST infrastructure has been recently built. The analysis is based on the estimation of disaggregated Nested Logit models using information provided by travellers in the main corridors: Madrid-Zaragoza and Madrid-Barcelona. The utility specification considers the effect of the main level-of-service attributes as well as some latent variables on modal choice. We analyze demand response to various policy scenarios that consider the potential competition between HST and other modes as well as the willingness to pay for improved levels of service. The results highlight the low level of competition that the HST could exert over air transport services in Madrid-Barcelona corridor, showing that policy makers may have been very optimistic about the figures of traffic diversion from air that could be attained.
Keywords: 330; intermodal competition stated preference (SP); mixed RP/SP data; HST elasticities; willingness to pay